Perioperative nutritional management of colorectal cancer patients under the enhanced recovery after surgery concept - Zhang Fangyuan; Chen Chunsheng; Zhang Hong (结直肠肛门外科)
Colorectal surgery is the professional field that recognizes and practices the concept of enhanced recovery after surgery (ERAS) during its early time. Perioperative nutritional management of patients undergoing colorectal surgery includes preoperative nutritional risk screening, pre-habilitation, perioperative bowel preparation, fasting, and postoperative nutritional management. Perioperative nutritional management is an important component when practicing ERAS and is critical for promoting early postoperative recovery of these patients. In this paper, we reviewed the current literature and evaluated perioperative nutritional management of colorectal cancer patients based on the ERAS concept.